Menuju Kesetaraan dalam Aturan Kewarisan Islam Indonesia: Kedudukan Anak Perempuan versus Saudara Kandung - Euis Nurlaelawati (JURNAL INDO-ISLAMIKA, 2012)
As response to the demand on women’s legal development, through the KHI Hukum Islam, Indonesia introduced a number of legal reforms on familial issues, including inheritance. Several legal reforms on inheritance issues include the rule of ahli waris pengganti, the rule of wasiat wajiba (obligatory bequest), and the rule of the share of daughters versus collaterals. These novel rules were introduced as to meet the demands of both solving contemporary legal issues and of empowering women to put them in equal position as men. This paper discusses the detailed rule on the share of daughter(s) when meeting collaterals in the case of inheritance as put forward in the KHI and its departure from the classical legal doctrines as found in fiqh texts. Using both bibliographical and field researches, which involve interviews with several judges and observation on judges’ decisions, this paper discovers that some judges continued to refer to classical legal doctrines and neglect the rule in the KHI. It also displays that there have been debate on the rule within both judges and legal scholars, demonstrating that the rule does not have firm legal Islamic rationale.